Review of Performance Based Contracting in the Road Sector : Phase 1 - Gericke, Ben (World Bank, Washington, DC, 2014)
There has been a tendency for a one-size-fits-all approach to the implementation, with the result being a variation in the success of any implemented performance based contracts (PBCs), as well as a significant proportion of the PBCs not making it to the contract award stage. To address these issues, the World Bank (WB) has commissioned a review of PBC in the road sector. PBC involves a significant shift away from more traditional approaches to the delivery and maintenance of road infrastructure and associated services by departing from the client's having responsibility for the design and supervision of construction and maintenance activities, to focus upon the key outcomes that the client wishes to achieve. There are two objectives for this study including: (1) to produce a strategy that will guide the WB's future engagements in PBC projects; and (2) to improve the WB's service to clients by offering a variety of PBC options, to suit different operating conditions and client needs. The report details phase one, review and synthesis of existing practices and its following six tasks: task 1, taking stock of various types of PBC projects; task 2, defining various types of PBC methodologies; task 3, outlining PBC's strengths and weaknesses; task 4, clarifying both various types of PBCs and federation internationale des ingenieurs-conseil (FIDIC)-type (input and bill of quantities) contracts; task 5, discriminating between successful and less successful factors of PBC projects; and task 6, developing a work program on how to move the second phase forward.